2022
DOI: 10.1002/adfm.202209471
|View full text |Cite
|
Sign up to set email alerts
|

Repair Strategies and Bioactive Functional Materials for Intervertebral Disc

Abstract: Intervertebral disc (IVD) degeneration is the leading cause of low back pain, which represents a highly prevalent chronic aging-associated disorder with a large socio-economic burden and a great decline in the quality of life, contributing to the pressing need for IVD treatments. Thus, finding effective disease-modifying approaches for postponing the progression of IVD degeneration and repairing degenerated intervertebral discs is of great importance, even facing various challengeable obstacles. Bioactive func… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 167 publications
(237 reference statements)
0
8
0
Order By: Relevance
“…An ideal hydrogel for the biological repair of the elastic, load-bearing intervertebral disc should have mechanical properties similar to those of the native disc, with appropriate buffering capacity and flexibility. , We thus tested the self-healing properties and mechanical performances of the GDC@EVs-GLRX3 hydrogel. When a piece of hydrogel was cut into two halves, they were able to merge and fuse into one within 20 min at 37 °C.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…An ideal hydrogel for the biological repair of the elastic, load-bearing intervertebral disc should have mechanical properties similar to those of the native disc, with appropriate buffering capacity and flexibility. , We thus tested the self-healing properties and mechanical performances of the GDC@EVs-GLRX3 hydrogel. When a piece of hydrogel was cut into two halves, they were able to merge and fuse into one within 20 min at 37 °C.…”
Section: Resultsmentioning
confidence: 99%
“…As the disc is a load-bearing organ, liquid drug alone is prone to leakage and inferior efficacy . Injectable hydrogels with locally retained EVs and sustained release for on-demand drugs are ideal formulas for intradiscal therapy. , In this study, we proposed a strategy that used an injectable, ROS-responsive, and EVs-GLRX3-loading hydrogel to balance the redox homeostasis in NP cells.…”
Section: Introductionmentioning
confidence: 99%
“…The biocompatibility experiments in vivo are helpful to eliminate the interference of other factors and can fully reflect the clinical transformation prospect. In the future, we will explore biocompatibility in vivo and tissue repair and regeneration associated with natural IVD [58][59][60] and monitor tissue rehabilitation after discectomy. [61]…”
Section: Mechanism Analysis Of Multidirectional Stiffnessmentioning
confidence: 99%
“…The pathogenesis of IDD featuring reduced NP cells with decreased extracellular matrix (ECM) synthesis has yet to be revealed clearly, 8 but it has been confirmed that oxidative stress (OS) and chronic inflammation often occur concurrently in the microenvironment of degenerated IVD. 9−11 Cell therapy has recently been applied to treat IDD for enhancing the NP cell number and ECM synthesis but failed to get the desired results, which is ascribed to the low proliferative index of NP cells and the difficulty in directed differentiation of stem cells in such pathological conditions.…”
Section: Introductionmentioning
confidence: 99%